Age and productivity : a sector perspective - Gan, Geraldine Xinya (2014)
In this study, we investigate the influence of sector size on productivity profile using a cross-country panel data. We theorize that different demands of the labour force necessitated by the different sectors results in varying productivity profiles. The findings that an expansion of the service industry will likely flatten the overall productivity profile suggest a relatively flat profile of the service industry. In contrast, an expansion of the agriculture sector may boost overall productivity of younger age groups. We also find that high income countries and ageing countries tend to have a later peak in productivity compared to low and low middle income and non-ageing countries respectively. The least productive sector is also likely to have more influence on the overall productivity profile. However, the investigations only analyse and identify broader global trends, providing underlying fundamentals for future empirical studies of the dynamics within sectors.